Analysis of the human VH gene repertoire. Differential effects of selection and somatic hypermutation on human peripheral CD5(+)/IgM+ and CD5(-)/IgM+ B cells. - Brezinschek, H P (1997)
To analyze the immunoglobulin repertoire of human IgM+ B cells and the CD5(+) and CD5(-) subsets, individual CD19(+)/ IgM+/CD5(+) or CD5(-) B cells were sorted and non-productive as well as productive VH gene rearrangements were amplified from genomic DNA and sequenced. In both subsets, the VH3 family was overrepresented largely as a result of preferential usage of a small number of specific individual family members. In the CD5(+) B cell subset, all other VH families were found at a frequency expected from random usage, whereas in the CD5(-) population, VH4 appeared to be overrepresented in the nonproductive repertoire, and also negatively selected since it was found significantly less often in the productive compared to the nonproductive repertoire; the VH1 family was significantly diminished in the productive rearrangements of CD5(-) B cells. 3-23/DP-47 was the most frequently used VH gene segment and was found significantly more often than expected from random usage in productive rearrangements of both CD5(+) and CD5(-) B cells. Evidence for selection based on the D segment and the JH gene usage was noted in CD5(+) B cells. No differences were found between the B cell subsets in CDR3 length, the number of N-nucleotides or evidence of exonuclease activity. Somatically hypermutated VHDJH rearrangements were significantly more frequent and extensive in CD5(-) compared to CD5(+) IgM+ B cells, indicating that IgM+ memory B cells were more frequent in the CD5(-) B cell population. Of note, the frequency of specific VH genes in the mutated population differed from that in the nonmutated population, suggesting that antigen stimulation imposed additional biases on the repertoire of IgM+ B cells. These results indicate that the expressed repertoire of IgM+ B cell subsets is shaped by recombinational bias, as well as selection before and after antigen exposure. Moreover, the influences on the repertoires of CD5(+) and CD5(-) B cells are significantly different, suggesting that human peripheral blood CD5(+) and CD5(-) B cells represent different B cell lineages, with similarities to murine B-1a and B-2 subsets, respectively.